Insect Management for Leafy Vegetables (Lettuce, Endive and Escarole) - Gregg S. Nuessly; Susan E. Webb (EDIS)
This document is ENY-475 (which replaces ENY-430, ENY-432, and ENY-440), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2002.